"They are grinding us into the ground" – The lived experience of (in)energy justice amongst low-income older households. (15th September 2018) - Willand, Nicola; Horne, Ralph
Highlights: Explores retrofits as capability enhancing mechanisms. Investigates social practices as functionings or enactments of capabilities. Reveals energy justice on four levels of social relationships on the home stage. Provides evidence of the multi-dimensional vulnerability of older householders. Advocates for minimum standards to protect people who lack capabilities and agency. Abstract: This article contributes to the literature on energy justice by revealing how the principles of energy (in)justice manifest at the domestic scale. We use data from a retrofit intervention trial to reveal recognised and hidden vulnerabilities and practiced distributive and procedural energy fairness in the lived experiences of low-income older and/or frail householders near Melbourne, Australia. Combining the capability and practice approach for the transition to lower carbon housing to provide a rich description, we chart householder functionings of heating and paying energy bills and their choices in keeping warm and affording energy before and after simple retrofits. Energy justice was experienced on four separately distinguishable levels of social relationships: intra-households, household-energy retailer relations, immediate social networks and wider social relations. The outcomes of the trial showed that combinations of simple retrofits improved householder heating capabilities. Policies and programs aimed at transitioning to low-carbon energy systems need to acknowledge and address the changing demand for energy of an ageing population, and acknowledge social differentiation within households. This includes using a capabilities approach to recognising multiple vulnerabilities.